2017
DOI: 10.1186/s12891-017-1498-0
|View full text |Cite
|
Sign up to set email alerts
|

Is coracohumeral distance associated with pain-function, and shoulder range of movement, in chronic anterior shoulder pain?

Abstract: BackgroundThe aim of this study was twofold: (i) to assess the intrarater reliability of coracohumeral distance; (ii) to investigate the level of association between coracohumeral distance measured by ultrasonography, and pain-disability and shoulder range of movement, in patients suffering from chronic anterior shoulder pain.MethodsAn observational, cross sectional study was carried out. A convenience sample comprised of 87 patients with chronic anterior shoulder pain was assessed from 3 primary care centres.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
12
2
Order By: Relevance
“…Navarro-Ledesma et al 16 reported poor correlation of a small CHD and shoulder function or pain in asymptomatic individuals. CHD can be influenced by gender, age, and arm position during MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Navarro-Ledesma et al 16 reported poor correlation of a small CHD and shoulder function or pain in asymptomatic individuals. CHD can be influenced by gender, age, and arm position during MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple studies, the reliability of CHD measurement by fluoroscopy, computed tomography, MRI, and ultrasound was proven. 3 , 7 , 10 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…The intra-observer correlation coefficient (ICC) was calculated by making measurements twice on each side of the same shoulders to evaluate the consistency of AHD measured by US, and the average values of the two measurements were used for the final statistical tests between groups. An ICC value less than 0.50 was an indication of "poor" reliability; "moderate" between 0.50 and 0.75, "good" between 0.76 and 0.90; and excellent over 0.90 [17]. One way ANOVA was used to compare the AHD values among the three research groups.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrasound examiner was blind to all measurements (values were obscured by placing a sticker on the ultrasound screen). A research assistant took the measurements and entered them into a database [17]. Sonographic AHD measurements were taken in millimetres.…”
Section: Outcome Measures Acromiohumeral Distance (Ahd)mentioning
confidence: 99%
“…Only 1 study 36 has analyzed the level of association between shoul-der pain and pectoralis minor length in a population with chronic shoulder pain, showing similar results (r = 0.09) to those obtained in the present study (r = 0.08). Moreover, other factors-such as the acromiohumeral distance, 37 the coracohumeral distance, 38 and shoulder-tendon thick-ness 39 have been studied in relation to chronic shoulder pain, also showing small associations.…”
Section: Discussionmentioning
confidence: 99%